Advocate marketing : strategies for building buzz, leveraging customer satisfaction, and creating relationships - Thomas, Barbara (Pearson Education, 2016)
Today, engaging customer advocates is one of the most powerful marketing strategies available to you. Advocates provide third-party validation and positive relevance; build and protect brands, and create exceptionally effective content to influence buyer decisions. Sales teams enjoy the benefits of advocates, too, through case studies, referrals/introductions, and assistance in securing renewals. Advocate Marketing: Strategies for Building Buzz, Leveraging Customer Satisfaction and Creating Relationships shows CMOs, business development leaders, and customer success professionals, and sales executives exactly how to leverage this powerful approach. Barbara Thomas helps you make the business case, outlines the strategic requirements, and presents powerful best practices and case studies. You'll learn from the experience of recognized leaders in advocacy marketing, from Intel and Citrix to Sirius Decisions, Influitive, Reputation Advocates, Boulder Logic, and RO/Innovations. Most important, Thomas introduces a systematic, five-step strategy for leveraging this powerful opportunity. You'll discover how to: Build a complete strategic plan for advocate marketing Define best-practice program processes and policies Establish internal resources, team, organizations, and budgets Choose and integrate the right technology and tools Establish and apply the right KPI metrics and analytics What others say about you carries far more weight than anything you can say about yourself. Advocate Marketing will help you transform that simple reality into a powerful competitive advantage.